Festivals as a Communicative Space in Assam and Arunachal Pradesh Borderland: A Study of Ali-Aye-Ligang and Solung - Doley, Pranjit; Koijam, Sunil (South Asian Journal of Social Sciences and Humanities, 2025)
This study investigates the role of festivals as space for communication that enhance interethnic relationships. By concentrating on the Ali-Aye-Ligang and Solung festivals within the Mishing and Adi communities, it analyzes how cultural expressions and mutual engagement facilitate intercultural dialogue and promote social unity. Employing a qualitative ethnographic methodology, data were collected through interviews and participant observation during the festival cycles of 2023-2024. The analysis illustrates how these festivals function as venues for cultural negotiation. Moreover, the results indicate that festivals serve as grassroots mechanisms for peacebuilding, fostering mutual understanding, and enhancing community resilience in a politically sensitive and ethnically diverse borderland. Rather than being simple celebrations, Ali-Aye-Ligang and Solung emerge as essential communicative actions that transform the borderland into a realm of coexistence and shared cultural identity.